2020
DOI: 10.1038/s12276-020-0379-z
|View full text |Cite|
|
Sign up to set email alerts
|

Isocitrate dehydrogenase 2 protects mice from high-fat diet-induced metabolic stress by limiting oxidative damage to the mitochondria from brown adipose tissue

Abstract: Isocitrate dehydrogenase 2 (IDH2) is an NADP +-dependent enzyme that catalyzes the oxidative decarboxylation of isocitrate to α-ketoglutarate in the mitochondrial matrix, and is critical for the production of NADPH to limit the accumulation of mitochondrial reactive oxygen species (ROS). Here, we showed that high-fat diet (HFD) feeding resulted in accelerated weight gain in the IDH2KO mice due to a reduction in whole-body energy expenditure. Moreover, the levels of NADP + , NADPH, NAD + , and NADH were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
(37 reference statements)
1
26
0
Order By: Relevance
“…IDH2 is a mitochondrial localised enzyme within the TCA cycle that catalyses the oxidative decarboxylation of isocitrate to alpha-ketoglutarate and a reduction in NADP to NADPH + levels 40 , 41 . Consequently, IDH2 is required for efficient energy substrate metabolism and redox signalling 40 . Considering our observations that muscles with reduced Yap levels display impaired fatty acid oxidation, features of lipotoxicity and lower alpha-ketoglutarate levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IDH2 is a mitochondrial localised enzyme within the TCA cycle that catalyses the oxidative decarboxylation of isocitrate to alpha-ketoglutarate and a reduction in NADP to NADPH + levels 40 , 41 . Consequently, IDH2 is required for efficient energy substrate metabolism and redox signalling 40 . Considering our observations that muscles with reduced Yap levels display impaired fatty acid oxidation, features of lipotoxicity and lower alpha-ketoglutarate levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, under chronic metabolic-thermogenic conditions such as obesity, excessive levels of ROS are produced which promotes mitochondrial damage in the BAT (Cui et al, 2019;Kazak et al, 2017;Lee et al, 2020) , . However, it is largely unknown whether and how NO bioactivity, another key redox mediator, modulates BAT function in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…This redoxmediated modulation leads to activation of UCP1-dependent uncoupling (Chouchani et al, 2016). In contrast, studies have shown that excessive ROS and RNS impairs BAT mitochondrial function (Cui et al, 2019;Lee et al, 2020). We then determined whether UCP1 is targeted by SNO using immunohistochemistry and biotin switch analyses.…”
Section: Obesity Elevates Protein S-nitrosylation and Decreases Cellumentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis was performed as described previously [21]. Briefly, protein samples were collected from the liver tissues of 24 h-fasted and fed WT and LKO mice, as well as from LRH-1 agonist-treated HepG2 cells.…”
Section: Western Blot Analysismentioning
confidence: 99%